2005
DOI: 10.1099/vir.0.80959-0
|View full text |Cite
|
Sign up to set email alerts
|

Immune responses of pigs after experimental infection with a European strain of Porcine reproductive and respiratory syndrome virus

Abstract: The purpose of this experiment was to study the immune response of pigs during an experimental infection with a European strain of Porcine reproductive and respiratory syndrome virus (PRRSV). Five pigs were challenged intranasally with PRRSV strain VP21 and another five were kept as controls. Clinical course and humoral and cell-mediated responses were monitored for 70 days post-infection (p.i.). Infected pigs developed mild signs at 24 h p.i. Viraemia was detectable by nested RT-PCR until day 14 p.i. Earliest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

20
114
1
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 183 publications
(137 citation statements)
references
References 50 publications
20
114
1
2
Order By: Relevance
“…These results were similar to those obtained in experimental PRRS infections, where the highest levels of serum Hp were found at the time of seroconversion of pigs (4 times higher than those obtained at the beginning of the experiment; Díaz et al, 2005). Moreover, in previous field investigations, serum Hp levels were also markedly increased after exposure to the PRRSv in pigs at 8 to 10 weeks of age from a farm with chronic PRRSv infection (Asai et al, 1999).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…These results were similar to those obtained in experimental PRRS infections, where the highest levels of serum Hp were found at the time of seroconversion of pigs (4 times higher than those obtained at the beginning of the experiment; Díaz et al, 2005). Moreover, in previous field investigations, serum Hp levels were also markedly increased after exposure to the PRRSv in pigs at 8 to 10 weeks of age from a farm with chronic PRRSv infection (Asai et al, 1999).…”
Section: Discussionsupporting
confidence: 88%
“…Longitudinal studies have been used to assess the evolution of selected APP in serum at specific times during the clinical course of experimentally induced viral diseases such as African Swine Fever and Aujeszky's disease (Carpintero et al, 2007), PRRS (Díaz et al, 2005) and also in bacterial infections with Streptococcus suis (Sorensen et al, 2006), Haemophilus parasuis (Martín de la Fuente et al, 2009) or Actinobacillus pleuropneumoniae (Lauritzen et al, 2003). Under field conditions, APP have been monitored in pigs during the clinical course of post-weaning multisystemic wasting syndrome (PMWS; Grau-Roma et al, 2009) and in pigs with PRRS virus (PRRSv) chronic infections (Asai et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Virus-neutralizing (VN) antibodies against PRRSV protect against viremia, virus replication in lungs, transplacental spreading of the virus and reproductive failure [12][13][14]20]. However, VN antibodies only appear in low amounts around 4 weeks or more after PRRSV infection, which is in contrast with the fast appearance of high amounts of nonneutralizing antibodies [7,34]. Attenuated as well as inactivated PRRSV vaccines are frequently used in the field.…”
Section: Introductionmentioning
confidence: 73%
“…Research interest has been focussed on the study of pig APP response in experimental acute inflammation and bacterial infections, as well as in farm animal manipulations [7,18,21,28,31,39,42]. Although there have been studies about virus infections in pigs [2,11,35,38], little is known about the APP response elicited by these pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…It has often been suggested that in humans, viral infections caused a weaker response compared to that of acute bacterial infections [41]. However, not much is known about APP response elicited by viruses in pigs [2,11,35,38]. The aim of this work was to give a general view of the APP response elicited during two relevant viral infections that have been extensively studied in swine: African swine fever (ASF) and Aujeszky's disease (AD).…”
Section: Introductionmentioning
confidence: 99%